City of fallen angels - Clare, Cassandra (New York : Margaret K. McElderry Books, 2011)
As mysterious murders threaten the new peace between Shadowhunters and Downworlders, only Simon, the Daylighter vampire, can help bring both groups together.
Keywords: Supernatural -- Juvenile fiction; Vampires -- Juvenile fiction; Demonology -- Juvenile fiction; Magic -- Juvenile fiction; New York (N.Y.) -- Juvenile fiction; Fantasy fiction